Penggunaan Media Animasi Untuk Meningkatkan Hasil Belajar IPS Tentang Keanekaragaman Budaya Indonesia Siswa Kelas V SDN Cangkringsari Sukodono Sidoarjo - Zuni Eka Tiyas Rifayanti (Prodi PGSD FIP UNM, 2017)
This class action research aimed to increasing student learning result through the utilization of animation media on social science. The subject of research is 20 fifth grade students of SDN Cangkringsari Sukodono Sidoarjo. The execution of this research consisted of two cycles and each cycle consisted from several stage namely planning, execution, observation and reflection. The kind of data that collected on this research are teacher’s learning activities, student’s learning activities and data from student learning result after the application of animation media. Data collected done by multilevel scale systematic observation method to measuring the activity of teacher and student while student learning result using evaluation tool in the form of test. On the data collection activity researcher helped by one observer. Data from this research analyzed descriptive qualitatively. When the process of learning goes well on cycle I and cycle II showing that teacher activity can increased, it indicated by the enhancement of teacher activity on first cycle with percentage as big as 64.16% and on the action of second cycle with percentage as big as 86.66% with the enhancement as big as 22.50%. Student’s activity on learning activity showing an enhancement from first cycle to second one, on first cycle with percentage as big as 62.69% and on the action of second cycle with percentage as big as 83.05% with the enhancement as big as 20.36% . On the student learning result that obtained from first cycle and second cycle, obtained average learning result score on first cycle as big as 61.75, and on the second cycle as big as 79.75 it showed that after the utilization of animation media on the matter of diversity of Indonesian’s cultures can increasing the learning result of fifth grade students of SDN Cangkringsari Sukodono Sidoarjo. Thus, utilization of animation media on the matter of diversity of Indonesian’s cultures can increasing teacher’s activity, student’s activity and student learning result. Keywords: animation media , social science learning, student learning result.